2016
DOI: 10.1111/nph.14057
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrification inhibition by rice root exudates and its relationship with nitrogen‐use efficiency

Abstract: Microbial nitrification in soils is a major contributor to nitrogen (N) loss in agricultural systems. Some plants can secrete organic substances that act as biological nitrification inhibitors (BNIs), and a small number of BNIs have been identified and characterized. However, virtually no research has focused on the important food crop, rice (Oryza sativa). Here, 19 rice varieties were explored for BNI potential on the key nitrifying bacterium Nitrosomonas europaea. Exudates from both indica and japonica genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(117 citation statements)
references
References 61 publications
2
82
3
Order By: Relevance
“…Some crops are able to produce nitrification inhibitors during a process called biological nitrification inhibition (BNI). This has been demonstrated in a tropical grass species, for rice (Sun et al, 2016), wheat (O'Sullivan et al, 2016, millet, peanut and sorghum (Subbarao et al, 2013;Li et al, 2018). It is possible to extract and use BNI substances from plants.…”
Section: Table 15mentioning
confidence: 95%
“…Some crops are able to produce nitrification inhibitors during a process called biological nitrification inhibition (BNI). This has been demonstrated in a tropical grass species, for rice (Sun et al, 2016), wheat (O'Sullivan et al, 2016, millet, peanut and sorghum (Subbarao et al, 2013;Li et al, 2018). It is possible to extract and use BNI substances from plants.…”
Section: Table 15mentioning
confidence: 95%
“…The presence of suberin lamellae was detected by yellow-green fluorescence (white arrowheads); the presence of lignin was detected by orange-red staining (black arrowheads). Bars = 100 μm 2003; Oburger et al 2014;Pearse et al 2006;Sun et al 2016). There is good information on angiosperm species in specific families that do or do not produce an exodermis; the vast majority of angiosperms does produce an exodermis (Perumalla et al 1990).…”
Section: Susceptibility To Pathogens: the Role Of Suberised Endodermimentioning
confidence: 99%
“…In further studies, it was found that some plant species synthesized important organic compounds and released these compounds into surrounding soils via roots [60]. These compounds were found being able to inhibit nitriication process, imposing similar Biological nitriication inhibitors generally including phenolic compounds, alkaloid, isothiocyanate and terpenoid [60,61]. For example, chemicals produced by Arbutus unedo, including phenolic compounds gallocatechin and catechin were able to decrease soil N 2 O emissions [62].…”
Section: Biological Nitriication Inhibitorsmentioning
confidence: 99%